Research on the Current Status and Trends of AIGC Integration Among Art and Design Students - Wu, Jiabao; Chen, Yongchuan (Journal of Research in Vocational Education, 2025)
With the rapid development of Artificial Intelligence Generated Content (AIGC) technology, it has gradually permeated design education. This study explores the application of AIGC among design students in higher vocational education, focusing on the relationship between their cognitive levels and application perceptions. Using the Technology Acceptance Model (TAM) and self-efficacy theory, surveys and semi-structured interviews were conducted.The study finds that students generally understand the core principles and interfaces of AIGC but have a weaker grasp of more complex algorithms, such as diffusion models. Students believe AIGC enhances design efficiency and stimulates creativity, though concerns remain about its adaptability in complex tasks.Significant differences were found based on grade level, with second-year students showing higher cognitive levels and application perceptions than first-year students. However, gender and academic major had no significant impact on AIGC cognition and application perception. Key factors influencing AIGC adoption include achievement experiences, peer influence, teacher guidance, and emotional states. Positive experiences and feedback significantly boost students’ willingness to adopt AIGC, while negative emotions may hinder this willingness.The findings provide insights for design course reform in vocational education, suggesting that personalised support based on students’ cognitive differences, as well as emotional management, is essential for overcoming initial technological barriers.